School Education System and Integrated Based Curriculum - Fitriyani Kosasih; H. ICE. Mubarok; Cepi Nurzaman (Edumaspul: Jurnal Pendidikan, 2023)
There is a tendency for teachers to package student learning experiences firmly compartmentalized between one field of study and another, learning that separates the presentation of subjects firmly will only make learning difficult for students because such separation provides an artificial learning experience. This research uses a qualitative approach using descriptive methods. The data collection technique uses in-depth interviews, observations, documents, and questionnaires. The results showed that 1. The integrated education carried out is to integrate Islamic boarding school education and education in schools which refers to the typical curriculum of the Integrated Salafi Islamic Boarding School Darussyifa Al-Fithroh, Sukabumi Regency. 2. The integration-based curriculum that exists at Yaspida Sukabumi Islamic College is a curriculum that integrates the pesantren and school curriculum with components of an integrated-based curriculum, community-based curriculum, competency-based curriculum, and amaliah worship-based curriculum